2002
DOI: 10.3989/scimar.2002.66n3313
|View full text |Cite
|
Sign up to set email alerts
|

Differences in diet between the two largest breeding colonies of Audouin's gulls: the effects of fishery activities

Abstract: SUMMARY: We analysed and compared the diet of Audouin's gulls Larus audouinii between their two largest breeding sites in the world: the Ebro Delta and the Chafarinas Islands (western Mediterranean). These two localities showed marked differences in the features of the commercial fishing fleet: in the Ebro Delta area a large fishing fleet produced large amounts of discards, while in the Chafarinas the fleet discarded smaller amounts of fish and marine invertebrates, due to the smaller number of vessels. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, discards were not uniformly available within the known foraging range of this species during the breeding season. Several studies have shown the relative contribution of supplementary food in gull diets is related to accessibility of these resources (Oro 1995, Bertellotti and Yorio 1999, Pedrocchi et al 2003, Duhem et al 2005, Ramos et al 2009). Thus, the extent of discard use and its potential effect on breeding success in a given locality would depend on the spatio-temporal pattern of vessel distribution.…”
Section: Discussionmentioning
confidence: 99%
“…However, discards were not uniformly available within the known foraging range of this species during the breeding season. Several studies have shown the relative contribution of supplementary food in gull diets is related to accessibility of these resources (Oro 1995, Bertellotti and Yorio 1999, Pedrocchi et al 2003, Duhem et al 2005, Ramos et al 2009). Thus, the extent of discard use and its potential effect on breeding success in a given locality would depend on the spatio-temporal pattern of vessel distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Gebbink et al (2011b) also reported minimal relationships between PFASs concentrations and carbon and nitrogen stable isotopes levels in Larus argentatus eggs in a long term study from Laurentian Great Lakes, which indicates the complexity of aquatic and terrestrial food as a source of PFASs to gulls. This supports the idea that L. Audouinii is amplifying their feeding habits exploiting increasingly other food resources such as continental preys or refuse dumps (Pedrocchi et al, 2002).…”
Section: Pollutant Correlation Between Eggs From the Same Clutchsupporting
confidence: 79%
“…The most important threat comes from the concentration around 79% of the world population in only one breeding colony, the Ebro Delta, in Catalonia , but it can also exploit fishery discards and freshwater preys (i.e. american crayfish, Procamburus clarkii) (Pedrocchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although Audouin's gulls are considered a feeding specialist in catching clupeoids at night (Oro, 1998), they exploit discards from trawling fishery activities (70% in biomass), which are very predictable in space and time (Mañosa et al, 2007; Oro et al, 1997; Pedrocchi et al, 2002). We analysed the local industrial fishery's landing statistics from the four closest harbours within a 60 km radius of the colony.…”
Section: Methodsmentioning
confidence: 99%